2022
DOI: 10.1002/aic.17670
|View full text |Cite
|
Sign up to set email alerts
|

Formulating noncovalent interactions to predict structural transition in mixed guest hydrates

Abstract: This work aims at formulating the noncovalent interactions of the mixed guest hydrate lattices of sI and sII structures. The reduced density plots obtained at the B3LYP level with 6‐31G(d) split valence set unveil the crucial contributions of hydrogen bonding, dispersion, van der Waals interaction, and steric effects toward lattice stability. These contributions are rather unreported in the hydrate phase equilibrium modeling. With this research gap, we attempt to formulate the natural regularity in the nonstoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…Consequently, when the CO 2 and CH 4 molecules share a hydrate lattice, a nonuniform distribution of the lattice stericity is observed. A similar dependence of steric hindrances on the guests occupying the hydrate lattice is also reported by Dongre and Jana …”
Section: Basic Theory and Its Applicationsupporting
confidence: 84%
See 1 more Smart Citation
“…Consequently, when the CO 2 and CH 4 molecules share a hydrate lattice, a nonuniform distribution of the lattice stericity is observed. A similar dependence of steric hindrances on the guests occupying the hydrate lattice is also reported by Dongre and Jana …”
Section: Basic Theory and Its Applicationsupporting
confidence: 84%
“…A similar dependence of steric hindrances on the guests occupying the hydrate lattice is also reported by Dongre and Jana. 70 A slight shift in the distribution of the RDG is observed when salt is introduced in the vicinity of a hydrate lattice. Grouped sign (λ 2 )ρ is used to quantify the variations in RDG distribution.…”
Section: Basic Theory and Its Applicationmentioning
confidence: 99%
“…45 Such coexistence of sIItype cage leads to catalyzing structural transition in the copresence of ethane. In Figure 5d, the structural transition boundary predicted by our model with accommodating the correlations of Peyrovedin et al 31 is compared with the boundaries reported by Klauda and Sandler, 17 Dongre and Jana, 21 and Chen and Li. 36 It is evident that above the ice point (i.e., T > 273 K), there are similarities in the predicted composition vs temperature profiles, which are also reasonably close to the experimental data.…”
Section: Mixed Guestsmentioning
confidence: 61%
“…In fact, the vdWP model requires the identification of the same number of adjustable parameters (i.e., 3) per guest, but the model of Chen and Guo involves three to six adjustable parameters per guest. A few studies have leveraged quantum mechanical calculations to evaluate hydrate phase properties , and gain insights into their stability. , The observations obtained from such simulations are then used to reduce the parametric dependencies of the phase equilibrium estimates. Others choose to directly use these quantum mechanical calculations and directly simulate the phase equilibrium conditions of different hydrate structures. However, these methodologies remain convoluted and highly computationally expensive, making the regression-based models more suitable for use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation